2017
DOI: 10.3233/jad-170429
|View full text |Cite
|
Sign up to set email alerts
|

Pazopanib Reduces Phosphorylated Tau Levels and Alters Astrocytes in a Mouse Model of Tauopathy

Abstract: Hyperphosphorylation and aggregation of tau protein is a critical factor in many neurodegenerative diseases. These diseases are increasing in prevalence, and there are currently no cures. Previous work from our group and others has shown that tyrosine kinase inhibitors (TKIs) can stimulate autophagy, decrease pathological proteins, and improve symptoms in models of neurodegeneration. Here we examined the role of pazopanib in mouse models that express either human mutant P301L tau (TauP301L) or triple mutant am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 94 publications
0
23
0
Order By: Relevance
“… Abl abelson, AUC area under the curve, C max maximum plasma concentration, DDR1/2 discoidin domain receptors 1 and 2, IC 50 half-maximal inhibitory concentration, PDGFR platelet-derived growth factor receptor, T max time to C max A [ 78 ] B [ 49 ] C [ 39 ] D [ 79 ] E [ 58 ] F [ 66 ] G [ 80 ] H [ 81 ] I [ 53 ] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Abl abelson, AUC area under the curve, C max maximum plasma concentration, DDR1/2 discoidin domain receptors 1 and 2, IC 50 half-maximal inhibitory concentration, PDGFR platelet-derived growth factor receptor, T max time to C max A [ 78 ] B [ 49 ] C [ 39 ] D [ 79 ] E [ 58 ] F [ 66 ] G [ 80 ] H [ 81 ] I [ 53 ] …”
Section: Resultsmentioning
confidence: 99%
“…However, bafetinib failed to alter the level of α-syn in transgenic PD models and affect dopamine metabolism using the same IP dose compared to either nilotinib or bosutinib, albeit bafetinib was reported to alter autophagy [ 57 ]. The half-maximal inhibitory concentration (IC 50 ) of bafetinib to Abl is 62 nM and 56 nM to PDGFRα [ 58 , 59 ] with no affinity to PDGFRβ [ 42 ]. Bafetinib (INNO-406) development was aimed at extending the susceptibility spectrum of mutations to TKIs and increasing selectivity towards Abl to reduce clinical adverse reactions during treatment, e.g., cardiovascular and metabolic toxicities of nilotinib [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 and [29]) and C. elegans experiments showed that STI1 prevented Aβ toxicity in body wall muscle, we performed a number of assays to assess whether 3-5-month-old TgA-5xFAD mice present increased resilience to Aβ-toxicity. Firstly, we used the FD NeuroSilver staining kit, which labels degenerating neurons (axons and soma) [50,[63][64][65][66]. In the hippocampi of male mice, we found significantly more silver particles in TgA-5xFAD mice, compared to their 5xFAD controls (Fig.…”
Section: Reduced Neuronal Resilience In 5xfad Mice Overexpressing Sti1mentioning
confidence: 87%
“…Most notably, chemokine (C-C motif) ligand 4 (Ccl4) and S100a9 were found dramatically increased in the brain of cDKO mice, which were down-regulated by both environment enrichment and calorie restriction (Dong et al, 2007 ; Wu et al, 2008 ), while in our study, both genes were also down-regulated by NaB treatment. It has been shown that several AD-like mouse models with hyperphosphorylated tau and/or increased GFAP levels had significantly higher levels of Ccl4 (one of inflammatory markers, also known as MIP-1β; Dong et al, 2007 ; Javidnia et al, 2017 ), which might be a potential cerebrospinal fluid biomarker of AD (Trombetta et al, 2018 ). S100a9, as an inflammation-associated calcium binding protein, was proposed to participate in inflammatory-mediated events, intracellular calcium increase and iNOS generation contributing to neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%